Musical education in Brazil in the present: challenges and prospects - Brochado, Mariah (Faculdade de Ciências e Letras/Unesp, 2016)
The text discusses the aspects of music education in Brazil today, after its inclusion in school curriculum in 2008, which  hanged the LDB. We It should observe the legal aspects of this pedagogical neoproject, its contents and its methodological characterization, reflecting on his factual possibilities, and highlighting projects ever undertaken in the country's schools.